The nomenclature of Pandanus alkaloids / Ibtisam Abdul Wahab, Hannis Fadzillah Mohsin and Ummu Amirah Armayni - Abdul Wahab, Ibtisam; Mohsin, Hannis Fadzillah; Armayni, Ummu Amirah (Universiti Teknologi MARA, Perlis, 2012)
From the literature, only one percent of the total Pandanus species (Pandanaceae family) were analysed in the studies related to their secondary metabolites. Scientific publications offered neither a recent record of all Pandanus alkaloids, nor the suggestion of any classification of these biomolecules. Therefore, this paper is aimed to propose the unprecedented nomenclature of Pandanus alkaloids, following the inventory of their 26 natural alkaloids. From the examination, these specific compounds have a basic C9N-C9 molecular framework. For an example, in the arrangement of carbon atoms of Pandanamine, the first carbon (C-1) is counted at the heteroatom of oxygen and the second carbon is attached with the ketone group. The C-1 to C-9 was assigned with one lactone skeleton. In the meantime, C-11 to C-19 showed the second lactone moiety. Furthermore, this nomenclature is determined based on its amine group. Pandanamine, being a symmetrical secondary amine, is hypothetically a biogenetic precursor of the Pandanus alkaloids. It has a straight chain of anime group that undergoes intramolecular cyclisation to form heterocyclic amines such as pyrrolidine (five-membered ring), piperidine (six-membered ring) and indolizidine (five- and six-membered rings). Thus, the compound that consists of piperidine alkaloid was named as pandamarilactone. Meanwhile, the molecules having pyrrolidine alkaloid was referred as pandamarilactonine. Pandanamine has two lactone rings and this might be observed in all alkaloids that were isolated from Pandanus species. The proposed systematic classification of the above alkaloid was utilised as well, in order to characterise two novel alkaloids, Pygmauesamine A and B, which were purified from the dichloromethane extract of Pandanus pygmaeus. Such compounds owning the indolizidine ring might possess biological activities such as antibacterial, fungicidal and insecticidal properties. It is anticipated that this nomenclature could be applied indefinitely, due to the relatively small number of Pandanus' alkaloidal structures.